2017
DOI: 10.17718/tojde.285815
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Access Points Within the Online Classroom: Where Students Look for Information

Abstract: The purpose of this study is to examine the impact of information placement within the confines of the online classroom architecture. Also reviewed was the impact of other variables such as course design, teaching presence and student patterns in looking for information. The sample population included students from a major online university in their first year course sequence. Students were tasked with completing a survey at the end of the course, indicating their preference for accessing information within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Despite the issues related to poor or no internet connectivity that seem to be a serious problem that concerns teachers such as Nigerian in-service teachers [ 89 ], this study lends support to Ref. [ 86 ], who argued that teachers can draw upon multifarious communication modalities integrated within the classroom for a better likelihood of viewership from the learner's end. This is in response to the students' preference for the utilization of multiple communication means, such as texting, email, message board and other multimedia technology platforms.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Despite the issues related to poor or no internet connectivity that seem to be a serious problem that concerns teachers such as Nigerian in-service teachers [ 89 ], this study lends support to Ref. [ 86 ], who argued that teachers can draw upon multifarious communication modalities integrated within the classroom for a better likelihood of viewership from the learner's end. This is in response to the students' preference for the utilization of multiple communication means, such as texting, email, message board and other multimedia technology platforms.…”
Section: Resultssupporting
confidence: 59%
“…indicated that a question or two posed by learners must be responded to promptly by the teacher within 48–72 h. Supporting [ 84 ] is [ 85 ], who argues that a discussion forum permits access to students, which could be an effective avenue for the provision of general information relative to the course. The effective utilization of the tools intended for communication permits teachers to send valuable information to students, as this is one of the obligations of teachers [ 86 ]. contended that students' preference for accessing and receiving information was toward multiple areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can actively guide students to focus on courses and majors and form an overall ideological perception in their future work. Steele et al [ 1 ] explored the influencing factors of information placement within the framework of the online classroom. The sample population includes students in the first-year course sequence of a major online college.…”
Section: Introductionmentioning
confidence: 99%